AKUNTANSI PENERIMAAN PAJAK PARKIR DAN RETRIBUSI PARKIR DI KABUPATEN MALANG - Kumalasari W, Intan; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out whether the Revenue Accounting in Malang Regency Government is in compliance with the accrual-based SAP based on Government Regulation No. 71 of 2010 in recording and reporting the revenues of parking taxes and parking retribution. Qualitative research. The research data has been obtained from observation, documentation and interviews with the parties which are relevant to this research. The object of this research is the parking taxes and parking retribution on the Budget Realization Report in 3 (three) year periods i.e. 2012-2014. This research is conducted in Malang Regency Government in the DPPKA and the DPKI of Malang Regency. The research it shows that the recording accounting of the revenues of parking taxes and parking retribution which has been made by DPPKA and DPKI of Malang Regency has been prepared and presented based on the SAKD by the Regulation of the Minister of Home Affair No. 13 of 2006. In the local financial, The government of Malang Regency has not implemented the accrual-based SAP yet and they still implement cash based to accrual. The cash based is for the recognition of revenues, expenditures, and finances in the budget realization report and accrual based is for the recognition of assets, obligations, and equity fund in balance sheet.Keywords: Parking Taxes, Parking Retribution, Government Accounting Standard